Deontologizing social being: the human in the virtual world - Nahapetyan, Ovsanna (Bulletin of Yerevan University E: Philosophy, Psychology, 2024)
In our era of postmodernism, due to contradictions and unprecedented unrest, man has found himself in such a situation that it is becoming increasingly difficult to simultaneously evaluate the period lived and ensure the ontological stability of human existence. The problem is that modern globalization processes, on the one hand, expand the framework of the socio-cultural space and time of human existence and activity and include it in a new context of possibilities, on the other hand, however, as a result of all this, man is, as it were, alienated from the world he created and ontologically obvious, real and native, and finds a place of residence in the virtual world. Figuratively speaking, an unprecedented process of deontologization of the social and creation of a fundamentally different world has begun, as a result of which man gradually moves away from the once remarkable and soulful world and settles in an alien world without being, which seems to be a semblance of the original in which he lived. What this new world will ultimately be like is not entirely clear, because the fate of this new and desocializing man who has undertaken all this is also unclear, over whose head, as K. Jung would say, is the sky, under whose feet is shrouded in history and all of humanity lost in the mists of antiquity, and ahead is the abyss of the future.